USE OF MODERN INNOVATIVE PEDAGOGICAL TECHNOLOGIES IN TEACHING BIOLOGICAL SCIENCES - Teshajonova Mahliyoxon Ma’rufjon qizi (Journals Park Publishing, 2022)
With the independence of the Republic of Uzbekistan, fundamental reforms were implemented in the economic and social spheres. The main essence of these reforms is the all-round development of the young generation, their spiritual wealth, high potential, knowledge, skills and qualifications. As science is constantly developing, man is always searching and researching, trying to discover new things and improve the well-being of life. Therefore, today's students also try to acquire deep knowledge of the basics of science, acquire science news, think independently, and become an active participant in the educational process. It is necessary to apply pedagogical technologies to the educational process in order to increase the student's interests, satisfy their needs for learning, and activate their cognitive activity.
Keywords: Innovation, technology, methodology, Case study, SCORE, SWOT analysis, Sinkway